Structural and biochemical characterization of a novel aminopeptidase from human intestine - Tykvart, Jan; Bařinka, Cyril; Svoboda, Michal; Navrátil, Václav; Souček, Radko; Hubálek, Martin; Hradilek, Martin; Šácha, Pavel; Lubkowski, Jacek; Konvalinka, Jan (The Journal of biological chemistry, 2015)
N-acetylated α-linked acidic dipeptidase-like protein (NAALADase L), encoded by the NAALADL1 gene, is a close homolog of glutamate carboxypeptidase II, a metallopeptidase that has been intensively studied as a target for imaging and therapy of solid malignancies and neuropathologies. However, neither the physiological functions nor structural features of NAALADase L are known at present. Here, we report a thorough characterization of the protein product of the human NAALADL1 gene, including heterologous overexpression and purification, structural and biochemical characterization, and analysis of its expression profile. By solving the NAALADase L x-ray structure, we provide the first experimental evidence that it is a zinc-dependent metallopeptidase with a catalytic mechanism similar to that of glutamate carboxypeptidase II yet distinct substrate specificity. A proteome-based assay revealed that the NAALADL1 gene product possesses previously unrecognized aminopeptidase activity but no carboxy- or endopeptidase activity. These findings were corroborated by site-directed mutagenesis and identification of bestatin as a potent inhibitor of the enzyme. Analysis of NAALADL1 gene expression at both the mRNA and protein levels revealed the small intestine as the major site of protein expression and points toward extensive alternative splicing of the NAALADL1 gene transcript. Taken together, our data imply that the NAALADL1 gene product's primary physiological function is associated with the final stages of protein/peptide digestion and absorption in the human digestive system. Based on these results, we suggest a new name for this enzyme: human ileal aminopeptidase (HILAP).
Keywords: dipeptidylpeptidasa 4; střeva; Protein Degradation; krystalografie rentgenová; Endopeptidases; Dipeptidyl Peptidase 4; Protein Structure, Tertiary; glutamátkarboxypeptidasa II; terciární struktura proteinů; Gene Expression Regulation, Enzymologic; Aminopeptidase; molekulární sekvence - údaje; Amino Acid Sequence; PICS; Glutamate Carboxypeptidase II; Metalloprotease; Human Ileal Aminopeptidase; Intestinal Metabolism; molekulární modely; Crystallography, X-Ray; krysa rodu Rattus; Models, Molecular; X-ray Crystallography; Animals; lidé; Molecular Evolution; Humans; DPP IV Activity; regulace genové exprese enzymů; zvířata; Rats; endopeptidasy; sekvence aminokyselin; Molecular Sequence Data; Intestines